Strategi Kolaborasi Antara Orang Tua Dan Guru Dalam Intervensi Gangguan Bahasa Pada Anak Usia Dini Di Ra Tahfidz Al-Hasbi, Gunung Tua Iparbondar - Siti Nur Bahagia; Sartika Dewi Harahap; Apriyanti Harahap (Journal of Innovative and Creativity, 2025)
This study investigates the collaborative strategies between parents and teachers in intervening in language disorders among young children and identifies the underlying causal factors at RA Tahfidz Al-Hasbi, Gunung Tua Iparbondar. The research employed a qualitative approach with a case study design. The participants consisted of two young children with language disorders, two parents, and one teacher. Data were collected through observation, in-depth interviews, and documentation. Data were analyzed using Miles and Huberman’s model, which includes data reduction, data display, and conclusion drawing. The findings indicate that collaborative strategies were implemented through regular communication, continuity of language stimulation between school and home, habituation of children to daily conversations, vocabulary repetition, assignment of simple homework tasks, and positive reinforcement both in the classroom and at home. Identified causal factors included early childhood malnutrition, lack of language stimulation within the family environment, inconsistent parenting practices due to parents’ busy schedules, and limited family economic resources. The study concludes that consistent collaboration between teachers and parents plays a crucial role in supporting language intervention for young children, while a comprehensive understanding of causal factors is necessary to design more effective intervention strategies.